2020
DOI: 10.1101/2020.08.14.251744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abortive Intussusceptive Angiogenesis Causes Multi-Cavernous Vascular Malformations

Abstract: Mosaic inactivation of CCM2 in humans causes cerebral cavernous malformations (CCMs) containing adjacent dilated blood-filled multi-cavernous lesions. We used CRISPR-Cas9 mutagenesis to inactivate zebrafish ccm2 resulting in novel lethal multi-cavernous lesions in the embryonic caudal venous plexus (CVP) caused by obstruction of blood flow by intraluminal pillars. These pillars mimic intussusceptive angiogenesis; however, the pillars failed to fuse to split the pre-existing vessel in two. Abortive intussuscept… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 56 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…adrb1 -/embryo also displayed a marked decrease of blood flow in CVP (Supplementary Video 2, and Supplementary Figure 1B), A similar reduction of heart rate and contractility by 2,3-BDM, a cardiac myosin ATPase inhibitor, prevented CVP dilation (Figure .4F). We previously found that arresting blood flow prevents aberrant intussusceptive angiogenesis and the resulted CVP cavernomas in ccm2 CRISPR embryos 3 . Taken together, these data suggest that reduced blood flow secondary to reduced cardiac function accounts for the protective effect of loss of β1AR signaling on CVP lesions and on CCM.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…adrb1 -/embryo also displayed a marked decrease of blood flow in CVP (Supplementary Video 2, and Supplementary Figure 1B), A similar reduction of heart rate and contractility by 2,3-BDM, a cardiac myosin ATPase inhibitor, prevented CVP dilation (Figure .4F). We previously found that arresting blood flow prevents aberrant intussusceptive angiogenesis and the resulted CVP cavernomas in ccm2 CRISPR embryos 3 . Taken together, these data suggest that reduced blood flow secondary to reduced cardiac function accounts for the protective effect of loss of β1AR signaling on CVP lesions and on CCM.…”
Section: Discussionmentioning
confidence: 98%
“…Inactivation of CCM genes leads to increased endothelial KLF2 expression 17,18 , a transcription factor important in cavernoma formation 3,19 . Nevertheless, silencing of adrb1 did not prevent the expected increased endothelial klf2a 17…”
Section: Loss Of β1ar Does Not Prevent Increased Klf2a Expression In ...mentioning
confidence: 99%
See 3 more Smart Citations